2015
DOI: 10.1186/s12935-015-0165-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-191 contributes to radiation-resistance of two lung cancer cell lines by altering autophagy activity

Abstract: BackgroundLung cancer is the leading cause of cancer-related morbidity and mortality all over the world. Surgery resection, radiotherapy, chemotherapy, immunotherapy and combined treatments have been discovered and well established for treatments. However, low survival rate of five years after clinical treatments mainly due to recurrence of stress-resistant cancer cells calls for better understanding and new ideas. Our project aimed to understand the forming process of stress resistant lung cancer cells after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
(37 reference statements)
2
9
0
Order By: Relevance
“… 42 Moreover, it impairs tumorigenesis and metastasis in aggressive breast cancer 43 and inhibits radiation-resistance in lung cancer. 44 In our study, multivariate analysis revealed decreased expression of miR-191-5p was associated with poor survival and tumor recurrence in patients with COAD and acted as an independent prognostic factor for OS in COAD patients. Our findings regarding the prognosis and diagnostic potentials of miR-191-5p in COAD were supported by these studies in renal cell carcinoma, breast cancer, and lung cancer, 41 44 but opposed by other studies in AML, 37 hepatic cell carcinoma, 38 and intrahepatic cholangiocarcinoma.…”
Section: Discussionsupporting
confidence: 50%
“… 42 Moreover, it impairs tumorigenesis and metastasis in aggressive breast cancer 43 and inhibits radiation-resistance in lung cancer. 44 In our study, multivariate analysis revealed decreased expression of miR-191-5p was associated with poor survival and tumor recurrence in patients with COAD and acted as an independent prognostic factor for OS in COAD patients. Our findings regarding the prognosis and diagnostic potentials of miR-191-5p in COAD were supported by these studies in renal cell carcinoma, breast cancer, and lung cancer, 41 44 but opposed by other studies in AML, 37 hepatic cell carcinoma, 38 and intrahepatic cholangiocarcinoma.…”
Section: Discussionsupporting
confidence: 50%
“…We selected miR-140 as one of the most promising candidates for further analysis because: (1) we performed in silico analysis (https://www.genomatix.de/) and identified a putative NRF2 binding site in the miR-140 promoter region (−7844/−7835, the transcription start site set as default +1) (Fig. 3B, top panel); (2) miR-140 is significantly upregulated in lung cancer cells in response to irradiation [25]; and (3) miR-140 inhibits proliferation and stem cell self-renewal [26]. q-PCR analysis showed an increased expression level of miR-140 in irradiated HLFs.…”
Section: Resultsmentioning
confidence: 99%
“…miR-124 was identified to be significantly downregulated in radiation-resistant sub-cell lines. Other downregulated miRNAs included miR-191 and miR-205, which have been reported previously to be involved in radiation resistance in lung and breast cancer, respectively ( 14 , 15 ). It was demonstrated that overexpression of miR-124 was able to sensitize radiation-resistant cells to radiation by decreasing the cell survival fraction and viability, and identified that TXNRD1 is an important target of miR-124.…”
Section: Discussionmentioning
confidence: 95%